1998
DOI: 10.1099/00221287-144-8-2367
|View full text |Cite
|
Sign up to set email alerts
|

Intron polymorphism in small subunit rDNA of Nectria galligena

Abstract: PCR amplification of the small subunit (SSU) rDNA gene of 40 isolates of Nectria galligena revealed four length polymorphisms. PCR-RFLP analysis of the SSU rDNA gene divided the isolates into four categories similar, but not identical, to categories identified by Southem-RFLP analysis. Nucleotide sequence analysis revealed that isolates in three of the four SSU rDNA (18s) categories possess an intron of 363 bp, 1185 bp or 1423 bp at the NS 7 priming site. Isolates in the fourth category do not possess an intro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…An alternative approach is to target the small subunit (SSU, 18S) rDNA gene and analyse 18S sequence variation among the fungal isolates using denaturing gradient gel electrophoresis (DGGE; Lessa, 1992; Vainio and Hantula, 2000). Although the 18S rDNA gene is highly conserved in nature, several studies have reported intraspecific variation within introns occurring in the gene (Crockard et al., 1998). Microsatellite‐primed PCR (MP‐PCR) has also been used successfully in species and subspecies differentiation in many pathogenic fungal genera (Czembor and Arseniuk, 1999), including Colletotrichum (Freeman et al., 1996).…”
Section: Introductionmentioning
confidence: 99%
“…An alternative approach is to target the small subunit (SSU, 18S) rDNA gene and analyse 18S sequence variation among the fungal isolates using denaturing gradient gel electrophoresis (DGGE; Lessa, 1992; Vainio and Hantula, 2000). Although the 18S rDNA gene is highly conserved in nature, several studies have reported intraspecific variation within introns occurring in the gene (Crockard et al., 1998). Microsatellite‐primed PCR (MP‐PCR) has also been used successfully in species and subspecies differentiation in many pathogenic fungal genera (Czembor and Arseniuk, 1999), including Colletotrichum (Freeman et al., 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Group I introns have been characterized from the nuclear small subunit (nuSSU) rRNA gene of the Ascomycete fungi Pneumocystis carinii (Sogin and Edman 1989) and Nectria galligena (Crockard et al 1998). Single nuSSU rRNA group I intron sequences have been identified for B. bassiana (Suh et al 2001; GenBank AF280633) and B. brongniartii (Nikoh and Fukatsu 2000; GenBank AB027335), but intron structure and population diversity were not defined.…”
Section: Introductionmentioning
confidence: 99%
“…These include two Cryphonectra introns (2) and an intron from Tillrtiopsis flava (15). The fact that similar group IC4 introns are found in distantly related eukaryotic micro-organisms suggests that the Nectria 363 intron, in contrast to what was suggested by Crockard et al (3), has been gained by horizontal transfer during evolution.…”
mentioning
confidence: 76%
“…We have re-analysed the Nectria sequences reported by Crockard et al (3) and discovered that the smallest insertion (the 363 intron) contains a typical group I intron structure (Fig. la).…”
mentioning
confidence: 90%